Influence of insulin-induced hypoglycemia on the hemostatic and fibrinolytic system in patients with hypothalamicpituitary disorders - Mönig, H.; Zurborn, K.-H.; Bruhn, H. D. (Hämostaseologie, 1998)
In order to study the acute and prolonged effects of hypoglycemia on the hemostatic and fibrinolytic system we measured prothrombin fragment (F1+2), thrombin-antithrombin III complex (TAT), platelet factor 4 (PF4), β-thromboglobulin (âTG), factor VIII antigen (F VIII antigen), D-dimer, tissue-type plasminogen activator (t-PA) antigen, and plasminogen activator inhibitor (PAI-1) in 22 patients during insulin tolerance test. F1+2 and TAT increased significantly 15 and 90 minutes after administration of insulin, as did PF4 and âTG. At 4 and 24 hours, these parameters were not different from baseline. Factor VIII antigen was not significantly altered. D-dimer concentration did not change. However, the D-dimer/TAT ratio significantly decreased at 15 and 90 minutes but increased markedly above baseline at 4 and 24 hours. t-PA antigen was also found to be elevated at 15 and 90 minutes but had returned to baseline at 4 and 24 hours. PAI-1 concentration did not change. We conclude from these data that both coagulation and fibrinolysis are activated in the short-term response to acute insulin-induced hypoglycemia, followed by a prolonged activation of fibrinolysis. Our study may explain why patients undergoing insulin tolerance test, despite marked clotting and platelet activation, almost never develop thromboembolic complications.
Keywords: Hypoglycemia; hemostasis; fibrinolysis; thrombin markers